2018
DOI: 10.3390/ma11050686
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation and Improving Mechanisms of Diatomite-Modified Asphalt Mixture

Abstract: Diatomite is an inorganic natural resource in large reserve. This study consists of two phases to evaluate the effects of diatomite on asphalt mixtures. In the first phase, we characterized the diatomite in terms of mineralogical properties, chemical compositions, particle size distribution, mesoporous distribution, morphology, and IR spectra. In the second phase, road performances, referring to the permanent deformation, crack, fatigue, and moisture resistance, of asphalt mixtures with diatomite were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…The improvement of binding capacity promotes the formation of cross-linked network structure of SBS in the matrix. The results show that there is no obvious chemical reaction between the modifier and the bitumen in the forced mixing process when silica fume is used for modification, mainly the dispersion, mixing, adsorption and crosslinking between the phases, which is consistent with the research results of [ 17 , 29 , 30 ]. The cross-linking force between the network and the network will restrict the movement of matrix particles, which greatly reduces the fluidity of the system, and also reduces the segregation of modified asphalt to a certain extent, so that the stability of the compound modified bitumen is significantly improved, and it is favorable to the high temperature property and fatigue resistance of the compound modified asphalt, but it has a negative impact on the low temperature property of the compound modified asphalt due to its low fluidity.…”
Section: Resultssupporting
confidence: 88%
“…The improvement of binding capacity promotes the formation of cross-linked network structure of SBS in the matrix. The results show that there is no obvious chemical reaction between the modifier and the bitumen in the forced mixing process when silica fume is used for modification, mainly the dispersion, mixing, adsorption and crosslinking between the phases, which is consistent with the research results of [ 17 , 29 , 30 ]. The cross-linking force between the network and the network will restrict the movement of matrix particles, which greatly reduces the fluidity of the system, and also reduces the segregation of modified asphalt to a certain extent, so that the stability of the compound modified bitumen is significantly improved, and it is favorable to the high temperature property and fatigue resistance of the compound modified asphalt, but it has a negative impact on the low temperature property of the compound modified asphalt due to its low fluidity.…”
Section: Resultssupporting
confidence: 88%
“…In roads with heavy traffic, the proportion of the damaged pavement is increasing [1,2,3,4]. Findings have demonstrated that increasing the modulus of the asphalt mixture was an effective way to resist damages and extend the service life of the pavements [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve better performance, researchers have actively attempted to use different types of additives to improve the performance of asphalt mixtures, such as crumb rubber, polymers, or natural rubber [6][7][8]. Many researchers showed that fibers could improve the low-temperature performance and fatigue life of virgin asphalt mixtures [9,10].…”
Section: Introductionmentioning
confidence: 99%